Human and Bovine Dentin Composition and Its Hybridization Mechanism Assessed by FT-Raman Spectroscopy - L. E. S. Soares; A. D. F. Campos; A. A. Martin (Journal of Spectroscopy)
FT-Raman spectroscopy was used to study the human and bovine dentin and their interactions with adhesive systems. Ten human (H) molars and ten bovine (B) teeth were prepared exposing the dentin and then each specimen was divided into two parts. The resulted forty dentin segments were treated either with the total-etch one bottle adhesive (Prime & Bond 2.1, PB) or with the single-step self-etching adhesive (Xeno III, X) and divided into four groups: HPB (control), HX, BPB, and BX. Each group was analyzed by FT-Raman spectroscopy before and after the adhesive treatment. Six regions of the Raman spectrum were analyzed and the integrated areas of organic and inorganic peaks were calculated. Bovine untreated specimens showed higher peak area of PO4 3−ν2  content than in human specimens. Human untreated specimens had higher peak areas of PO4 3−ν4 and CO3 2−ν1  contents than in bovine specimens. The peak areas of amide III, CH2, and amide I contents were higher in human than in bovine specimens (before treatments). Treated dentin showed no significant statistical differences between the adhesives for both inorganic and organic contents considering the same substrate. However, the differences found between human and bovine specimens after adhesives application show a reduced accuracy of these substrates as a substitute to the human specimens.